Attracting and retaining personal care assistants into the Western Australia (WA) residential aged care sector. (2nd October 2017) - Dhakal, Subas; Nankervis, Alan; Connell, Julia; Fitzgerald, Scott; Burgess, John
ABSTRACT: The Australian population is ageing, with around one quarter being 60 years and older, and the proportion is expected to grow in the future. These trends have led to government projections for the number of personal care assistants (PCAs) needed to meet the demands of the ageing population, estimated to be more than double the current workforce by 2050. Consequently, the challenges associated with attracting and retaining PCAs in the aged care sector need to be urgently addressed. This qualitative study is based on a large and distributed residential aged care organisation located in Western Australia. Its focus is on the employment conditions of PCAs, their satisfiers and dissatisfiers, and the human resource management practices which might assist the organisation and its sector to better address PCA concerns, leading to more effective PCA attraction, selection and retention. A number of strategies have been proposed that are intended to help advance policy and debate, including attention to various HRM practices and factors relating to job quality.